Bioinsumos na cultura do milho: interações com manejo do solo e água - Guidinelle, Rebyson Bissaco (2023)
Faced with population growth and the growing demand for food, together with restrictions on natural resources essential to agricultural production, especially soil and water, it is crucial to investigate technologies that enable greater productivity, without depleting natural resources, with a conservationist approach. This implies reducing dependence on chemical inputs external to the productive agricultural ecosystem. Microbial bioinputs represent promising technologies due to their ability to modulate plant responses to overcome biotic and abiotic stresses. Furthermore, they demonstrate to be responsive in conservation-based environments, such as the no-till system. The use of waste in agriculture presents itself as a complementary alternative to this production system, as it allows the appropriate disposal of an environmental liability, such as, for example, wastewater from pig farming, with great potential for being used as fertilizer. The great virtue of this study is the generation of a technology that allows the joint use of bioinputs (efficient microorganisms), wastewater from pig farming and direct planting systems with a view to making agriculture less dependent on the use of human and industrial water supplies, as well as as well as fertilizers. Therefore, the objective of this study was to evaluate microbial bioinputs formulated with Herbaspirillum seropedicae (strain HRC54) and Azospirillum brasilense Ab-V5 (CNPSo 2083) and Ab-V6 (CNPSo 2084), applied as a single inoculum or co-inoculated, and to understand its action on maize cultivation (Creole maize, Fortaleza variety) in different soil conditions. These conditions were represented by different soil management systems: direct planting system and conventional planting system, irrigated with different levels of pig farming wastewater and raw water. To this end, three experiments were conducted, carried out in greenhouse and field conditions, in different treatment configurations, which are presented in three chapters of the thesis. In chapter 1, developed in a greenhouse, under co-inoculation conditions (H. seropedicae + A. brasilense), microbial bioinputs showed a synergistic effect on soil with higher biological quality. In chapter 2, carried out in a xii xii greenhouse, an experiment evaluated under water restrictions, it was noted that bioinputs had a more significant contribution to physiological attributes in treatments with a history of conventional planting systems, highlighting their effectiveness in mitigating abiotic stresses. In chapter 3, which was carried out under field conditions, the effects of coinoculation in different management systems were investigated. It was highlighted that the direct planting system, together with irrigation with wastewater from pig farming, created an environment more favorable soil conditions, providing a more favorable biological quality for the growth of the microbial population introduced into the system, which, in turn, allowed greater development of the maize crop.